L’hygiène dans les établissements agricoles gallo-romains à travers les auteurs antiques et les recherches archéologiques - Frédéric Devevey (In Situ)
Structures associated with the management of clean water and wastewater played a key role in the general organisation of the establishments of rural Antiquity, a role that was linked to questions of hygiene but which has been misunderstood or ignored by research for a long time. The existence of more or less elaborate bathing installations has long since been recognised and published for the ‘pleasure’ villas or the pars urbana of the vast agricultural estates of the countryside in Roman Gaul, but what of the smaller agricultural sites, the farms that, after all, represented the essential part of aggro-pastoral activity? According to the agronomical authors of classical antiquity, the ‘hygienic’ virtues of an environment were determined by physical characteristics. Water, the soil and the air underpin the salubrity of a site and its general hygiene which is a condition sine qua non for a viable exploitation. Does preventive archaeology find evidence of the application of these rules in the different rural establishments, the small agricultural villas, that have been excavated to date? How did the farmers on these small exploitations manage their hygiene in general and at individual levels? Does archaeological evidence reveal traces of the implementation of the recommendations of classical authors? This article presents a selection of Gallo-Roman establishments which have been excavated over the past ten years in the eastern part of the Dijon agglomeration, part of the territory of the Lingones. It completes a more general synthesis to be published shortly by Frédéric Devevey, Valérie Taillandier and Chloé Duseau on the uses of water in the agricultural exploitations of antiquity in the Dijon region. This study was carried out in the context of the Rurland programme on rural landscapes in north-eastern Roman Gaul, co-ordinated by Michel Reddé between 2012 and 2017.